Frequent and Recent Non-fatal Strangulation/Choking During Sex and Its Association With fMRI Activation During Working Memory Tasks - Huibregtse, Megan E.; Alexander, Isabella L.; Klemsz, Lillian M.; Fu, Tsung-chieh; Fortenberry, J. Dennis; Herbenick, Debby; Kawata, Keisuke (Frontiers in Behavioral Neuroscience, 2022)
Being strangled, or “choked,” by a sexual partner has emerged as a prevalent, and often wanted and consensual, sexual behavior among adolescent and young adult women, yet the neurological consequences of repeated exposure to this behavior are unknown. The objective of the study was to examine the association between a history of repeated, recent choking/strangling episodes during sex and fMRI activation during working memory tasks in young adult women. This case-control study involved young adult women (18 – 30 years old) at a large, public university, and consisted of two study groups: a choking group consisting of participants who were recently and frequently choked/strangled during sex by a partner (≥4 times in the past 30 days) and a choking-naïve (control) group who had never been choked/strangled during sex. Participants completed two variations of the N-back (0-back, 1-back, and 2-back) working memory task during functional magnetic resonance imaging (fMRI): a verbal and visual N-back tasks. Data from 20 participants per group were available for analysis. Between-group differences for accuracy and reaction time were not significant for either variation of the N-back task. Significant differences in fMRI activation patterns were detected between the choking and the choking-naïve groups for the three contrasts of interest (1-back > 0-back, 2-back > 0-back, and 2-back > 1-back). The choking group exhibited increased activation in multiple clusters relative to the choking-naïve group for the contrasts between the 1-back and 2-back conditions compared to the 0-back conditions (e.g., superior frontal gyrus, corpus callosum). However, the choking-naïve group exhibited increased activation relative to the choking group in several clusters for the 2-back > 1back contrast (e.g., splenium, middle frontal gyrus). These data indicate that recent, frequent exposure to partnered sexual strangulation is associated with different neural activation patterns during verbal and visual working memory tasks compared to controls, suggesting that being choked/strangled during sex may modify the allocation of neural resources at increasing levels of cognitive load. Further investigation into the neurologic effects of this sex behavior is warranted, given the prevalence of sexual choking among adolescent and young adult women.